Psychological capital, mobility, and the academic performance of military-connected elementary school students - Fowler, Tyler James (Kansas State University, 2023)
The purpose of this study was to examine military mobility as it relates to the education and academic performance of elementary school children of active-duty military service members. There are an estimated 1.5 million military dependents from ages 0-18. Nearly 35% of these dependents (521,930) are elementary-aged students between six and eleven years old. Military-connected students will move an estimated six to nine times during their K-12 educational careers. These moves will most likely be to different states and, possibly, different countries. Due to this frequent movement and different educational standards and curriculum from place to place, these students are at-risk of possibly developing academic gaps. The population of military-connected elementary school students is an understudied population in the existing published research. This study was divided into three articles for publication in peer-reviewed journals. The first article is a content analysis of peer-reviewed journals since 2001. Peer-reviewed journals were examined for content related to the academic performance of military-connected elementary students. These results show this population of students is grossly underrepresented. Thus, creating research space for the next two articles. The second article makes use of the psychological capital (PsyCap) theory to examine the possible correlations between overall PsyCap levels and levels of self-efficacy, hope, resiliency, and optimism (the four areas that make up PsyCap) and mobility levels in parents of military-connected elementary school students in kindergarten through 5th grade. Parents were also interviewed to determine if there were common structures, strategies, supports, and processes among families to facilitate successful transitions. The final article makes use of student assessment data from district (percentile rankings) and state (scaled scores) standardized assessments in the areas of reading/English language arts and mathematics. This article examines the correlations between assessment data and student stability levels. The findings of this study discovered minor correlations between parent mobility and levels of PsyCap. The areas of communication/records, community, school choice, and resources were found as categories of parental focus as families transition between duty stations. The study also determined a slight negative correlation between levels of stability and student academic performance on standardized assessments. Future research in this area should expand on the data collected in this study to include longitudinal data to examine possible effects of mobility on academics along with the possible social, emotional, and behavioral impacts.
Keywords: Military-connected; Elementary; Academic performance; Psychological capital; Mobility